External evaluation of learning as a guarantee of quality education - Arribas Estebaranz, José Mª (Avances en Supervisión Educativa, 2014)
The external evaluation of the academic performance of students and / or schools is an admittedly controversial right now-now-fully arouses strong opposition in many social and educational sectors.We present as aseptically as possible and with all scientific honesty arguments usually put forward and misgivings, many of which allude more perverse-effects often certain derivatives of malpractice that its very existence, the goodness or badness as in so many other spheres of life, depend to a large extent on its implementation: Why and what is assessed, how it is evaluated, what use is made of the results, what consequences follow from them ...Almost all countries and all reports use contemplated, in varying degrees, the always-complementary external evaluation by the teachers-as an essential guarantee of educational quality at different levels of detail curriculum evaluation.
Keywords: evaluation; quality of education; achievement control; school effectiveness; external evaluation